The Effectiveness of Blended Learning in Improving Students' Self-Regulated Learning in Islamic Religious Education Subjects: Efektivitas Blended Learning dalam Meningkatkan Self-Regulated Learning Siswa Pada Pelajaran Pendidikan Agama Islam - Bulqia Mas'ud; Hajina; Darwis (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2024)
In the era of the Industrial Revolution 4.0, leveraging technology in education is crucial. Self-Regulated Learning (SRL), which entails individuals' ability to understand and control their learning environment, fostering independence and responsibility, can be influenced by the blended learning model. This study, employing a mixed-methods design and a pre-experimental design for the quantitative phase, aimed to examine the impact of blended learning on SRL. Data were collected via questionnaires and analyzed with paired sample t-tests. The results showed that (1) the descriptive analysis of the SRL pre-test of students indicates that the highest percentage was in the medium category with 85% students; (2) the results of the SRL post-test proved that the highest percentage is in the low category with 63% students; and (3) the results of the paired sample t-test showed the value of sig. (2-trailed) < alpha (0.007 < 0.05). The statistical analysis confirmed a significant difference between pre-test and post-test scores, suggesting that the blended learning model was not effective in enhancing SRL among students in Islamic Education at SMKN 7 Majene. Observations and interviews revealed that students' lack of self-regulated learning was due to inadequate technological resources and challenges in using Google Classroom, which was a novel experience for students and hindered their ability to access materials and submit assignments. Abstrak Era revolusi industri 4.0, pemanfaatan teknologi dalam dunia pendidikan sangatlah penting. Self-Regulated Learning (SRL), yang melibatkan kemampuan individu untuk memahami dan mengontrol lingkungan belajar mereka, menumbuhkan kemandirian dan tanggung jawab, dapat dipengaruhi oleh model pembelajaran campuran. Penelitian ini, yang menggunakan desain metode campuran dan desain pra-eksperimental untuk fase kuantitatif, bertujuan untuk menguji dampak pembelajaran campuran pada SRL. Data dikumpulkan melalui kuesioner dan dianalisis dengan uji-t sampel berpasangan. Hasil penelitian menunjukkan bahwa (1) analisis deskriptif pre-test SRL mahasiswa menunjukkan bahwa persentase tertinggi berada pada kategori sedang dengan jumlah 85% mahasiswa; (2) hasil post-test SRL membuktikan bahwa persentase tertinggi berada pada kategori rendah dengan jumlah 63% mahasiswa; (3) hasil uji-t sampel berpasangan menunjukkan nilai sig. (2-tailed) < alpha (0,007 < 0,05). Analisis statistik mengkonfirmasi perbedaan yang signifikan antara skor pre-test dan post-test, menunjukkan bahwa model pembelajaran blended learning tidak efektif dalam meningkatkan SRL di kalangan siswa pada pelajaran Pendidikan Agama Islam di SMKN 7 Majene. Pengamatan dan wawancara mengungkapkan bahwa kurangnya pembelajaran secara mandiri disebabkan oleh sumber daya teknologi yang tidak memadai dan tantangan dalam menggunakan Google Classroom, yang merupakan pengalaman baru bagi siswa dan menghambat kemampuan mereka untuk mengakses materi dan mengumpulkan tugas.